Where Now are the Dreams of Youth - Hughes, Ed (bfi, 2011)
Horino, a rich student, cheats at exams and rejects potential brides. When his father dies and he inherits the company he helps his three friends cheat at the company's entrance exam. However, a conflict emerges when one of Horino's friends gets engaged to the woman he has feelings for. [www.bfi.org.uk]
Keywords: DVD-Video